Determinación de Impactos Ambientales y Propuesta de Plan de Manejo Ambiental en el Centro de Comercialización de Ganado Vacuno de la Ciudad de Machachi en el periodo 2016. - Titusunta López, Diego Alberto (2016)
The objective of this investigation was the determination of environmental impacts and the proposal of environmental management plan in the Center for Commercialization of Cattle in the City of Machachi, Canton Mejia, Province of Pichincha. It began by making field visits and observations to identify the main aspects and environmental impacts of the current situation of the Cattle Marketing Center. The methodology for rapid impact assessment and ecological evaluation was applied, using Leopold matrices for the assessment, quantification of impacts and a set of techniques that allowed to identify effectively the physical, biotic and socioeconomic aspects of the study area respectively. The activity flow diagram was defined with inputs and outputs. The soil water sample was collected and an analysis of the laboratory report was performed with the interpretation and comparison of results with the Ministerial Agreement 028, Table 1. Criteria of soil quality; Table 9. Discharge Limits to the Public Sewer System and Table 10. Discharge Limits to a Freshwater Body. A Proposal for an Environmental Management Plan was carried out with the objective of continuously improving the activities of the study area to mitigate, minimize environmental impacts and adapt the physical space according to the activities carried out at the fair. The proposed Environmental Management Plan addresses 9 programs that have their respective measures that allow the prevention and mitigation of the negative impacts generated by the activities associated with the operation, maintenance and abandonment of the study area. Finally, the appropriate design of the physical space and services was made using the SOFTWARE AUTOCAD 3D, which will allow to give an ideal projection of the fair's facilities for the preservation of the environment.